Port Site Metastasis of Breast Cancer after Video-Assisted Thoracic Surgery for Pulmonary Metastasis of Breast Cancer: A Case Report - Meehyun Park; Ji-Young Hwang; Su Jeong Hyun; Yul Lee; Ji Young Woo; Ik Yang; Hye Sook Hong; Han Myun Kim (대한영상의학회지, 2016)
We reported a case of port site metastasis in a 57-year-old patient who underwent video-assisted thoracic surgery (VATS) resection of pulmonary metastasis from breast cancer. Port site metastasis after VATS is very rare in patients with breast cancer. However, when suspicious lesions are detected near the port site in patients who have undergone VATS for pulmonary metastasis, port site metastasis should be considered in the differential diagnosis.